Feeling bad and Precious (2009): black suffering, white guilt, and intercorporeal subjectivity - Katariina Kyrölä (Springer, 2025)
The article draws on 24 essays where university students in Sweden reflect on their affective reactions to the American film Precious: Based on the Novel Push by Sapphire (2009). The essays pay particular attention to how scenes of Black suffering and the body of the character Precious called forth feelings immediately as well as more enduringly, and how participants’ cultural situatedness directed the reactions and reflections. The article asks how seemingly unintentional, affective reactions intertwine with reflexive practices in film viewing and analysis, when both are understood as intercorporeal processes of subject formation. Especially intense moments of ‘feeling bad’ spurred the writers to dissect and question the need for ‘sameness’ or ‘difference’ between themselves and the bodies on-screen as incentives for engagement. Drawing on Black feminist thought and theorizations of affect, the article examines how ‘feeling bad’ can mobilize ethical subjectivities in encounters with racialized suffering and injustices.